10 Years of Open Access Society Publishing. Issue 1 (30th December 2020) - Novara, Francesca Rita
Abstract : That was ten, this is now ! The Editor‐in‐Chief of ChemistryOpen Francesca Novara discusses what 2020 meant for the development of open science and ChemistryOpen and what is the landscape in which ChemistryOpen will celebrate its 10th anniversary.